Efektifitas Penggunaan Kombinasi Metode BASOKU dan Pola Makan Terhadap Peningkatan Produksi ASI di PMB Santi Yosina Kecamatan Syamtalira Bayu Kabupaten Aceh Utara - Khalidah Khalidah; Eka Sutrisna (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
Smooth milk production is very important to meet the baby's nutritional and nutritional needs. One of the most effective methods to increase milk production and reduce mother's stress while breastfeeding is to combine the BASOKU method (breastcare, oxytocin massage and husband's support) and regulate diet. This method is by doing breast massage, oxytocin massage on the spine as an effort to release the hormone oxytocin which can stimulate more milk production, coupled with the husband's support in exclusive breastfeeding for his baby. Mother's diet regulation that can increase milk production.The aim of the study was to determine the effectiveness of the combination of the BASOKU method and diet on increasing breast milk production at PMB Santi Yosina, Syamtalira Bayu District, North Aceh Regency.This type of research is a quasi-experimental research with a two-group posttest only design. The stages of the research are: The first stage of this research is to explain to postpartum mothers and their families about the BASOKU method and the diet that will be applied to mothers. The second stage is monitoring the increase in infant weight gain in those who receive treatment and those who do not receive the BASOKU method and diet. The population of this study were all postpartum mothers who gave birth at PMB Santi Yosina. The sample in this study used purposive sampling as many as 17 people in the control group and 17 people in the treatment group. Data were analyzed using paired t-test.The study was conducted from April to September 2021. The results of the univariate analysis showed that most of the increase in breast milk production in postpartum mothers in the intervention group in the 140-200 gram category was 15 people (88.2%) while in the control group in the <140 category. grams by 14 people (82.4%). The results of the bivariate analysis showed that there was a difference between the combined use of the BASOKU method on increasing breast milk production in postpartum mothers with a p value of 0.000. The technology readiness level of this research is 2.